Biomarkers for an early diagnosis of immune effector cell associated-hemophagocytic syndrome - Edoardo Campodonico; Edoardo Campodonico; Piera Angelillo; Matteo Doglio; Alessia Ugolini; Maria Teresa Lupo Stanghellini; Maddalena Noviello; Maddalena Noviello; Elena Tassi; Elena Tassi; Federica Pedica; Federica Pedica; et al. (Frontiers in Immunology)
Hemophagocytic lymphohistiocytosis (HLH) is a hyper-inflammatory syndrome characterized by deficient NK-cell activity, cytokine storm and altered T-cell immunity, potentially sustained by multiple triggers. Recently, a hyperinflammatory condition resembling HLH has emerged as a potential complication of CAR T-cells. HLH represents a diagnostic conundrum due to its rarity, non-specific presentation and lack of validated biomarkers. We investigated a panel of serum cytokines which represent candidate markers to diagnose HLH after CAR-T. We analyzed 2 patients affected by B-cell lymphomas who received anti-CD19 CAR-T and developed HLH defined according to multiple diagnostic criteria. We identified four controls who did not develop HLH: one with CRS without cytopenia, one with cytopenia with CRS, one with both and one with none. We selected a set of acute-phase molecules including CD163, IL33R (quantitated through ELISA), CTLA-4, and CD80 (quantitated through Luminex) and studied their trend in frozen sera collected at parallel time-points. We studied case sera and compared them with controls. All patients developing CRS showed an early peak in IL2R, CD80, CTLA-4 and IL33R, followed by a second, more marked increase in case of HLH, absent in controls. The kinetics of the selected markers suggests that timing and extent of changes might help discriminating HLH from other causes of fever or cytopenia. Serum CD163, CTLA-4, CD80 and IL33R deserve prospective assessment as promising biomarkers to assist in the differential diagnosis between CRS, HLH and non-inflammatory cytopenias after CAR-T.